Inequality, Perception Biases and Trust - Markus Knell; Helmut Stix (Oesterreichische Nationalbank (OeNB), 2017)
We present a theoretical framework that links trust, trustworthiness and inequality. It is assumed that an individual's level of interpersonal trust is related to expected trustworthiness among his reference group and that trustworthiness decreases when interpersonal income differences increase. As a consequence, inequality affects trust via the individual-specific perception of inequality which might not coincide with aggregate measures of inequality like the Gini coefficient. We work out the implications of our model for empirical estimations of the trust-inequality nexus and show that such regressions are very likely to understate the true effect of inequality. This might lead to the erroneous conclusion that inequality exerts no effect on trust. Survey data from Austria support the predictions of our framework. Individual-specific perceptions of inequality have a strong negative effect on trust while aggregate measures of inequality show no significant relation.
Keywords: 330; Trust; Inequality; Perception